(untitled) (Journal of the College of Education for Women, 2019)
Allah created the human from clay and made the system of marriage between maleand female as a reason for life continuity and human staying. This system produced anorganization called (the society) which is defined as a group lived in limited time and place.Islam put fundamental and conditions of the righteous society in the Holy Quran andprophetic sunna. Islam also put the solutions for problems (if they got) , naturally, theseproblems may happened because of the nature of the life.The problem of the research is summarized by that the problems of the societyenlarged in our Islamic society more than time ago. In the same time , some solution areimported from west and east and from scientist and ignorant with ignoring the propheticsolutions for these problems